Kidney Transplantation for Erdheim-Chester Disease. (13th July 2020) - Yoo, Jongwon; Gunsteen, Cynthia; Patel, Sima; Clevy-Schneller, Ted; Nand, Sucha; Jain, Divya; Garcia-Roca, Raquel; Desai, Amishi; Akkina, Sanjeev
Abstract : Erdheim-Chester disease is a rare inflammatory disease that infiltrates skeletal and extra-skeletal tissue. Chronic kidney disease (CKD) in Erdheim-Chester disease is usually attributed to retroperitoneal lesions that lead to urologic obstruction and hydronephrosis. In this report, we describe a patient diagnosed with Erdheim-Chester disease who eventually developed end-stage kidney disease (ESKD). After complete remission of Erdheim-Chester disease by vemurafenib therapy and 2 years of hemodialysis, the patient underwent a deceased donor kidney transplantation with basiliximab induction and tacrolimus/mycophenolic acid maintenance. After conversion of mycophenolic acid to azathioprine due to cost, acute cellular rejection had occurred, and he was treated with steroid therapy. The patient remained in complete remission from Erdheim-Chester disease and dialysis-free 16 months after transplant. Kidney transplantation is another treatment option for those patients with Erdheim-Chester disease who suffer from renal failure in the setting of complete remission.